PROGRAM MAGANG MAHASISWA SEBAGAI MODEL PENGABDIAN DALAM PENGUATAN TATA KELOLA ADMINISTRASI DI PT PRAKARSA TANI SEJATI - Sartika Miming; Eligia Monixa Salfarini (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
Internship programs are a form of experientail learning that provide students with opportunities to apply their knowledge and skills in a professional work environment. This article aims to describe the implementation of a student internship program in supporting the strengthening of administrative governance at PT Prakarsa Tani Sejati. The method used was a descriptive approach through direct involvement in various administrative activities whitin the company. The activities included document archiving, correspondence administration, document digitization, data processing, and report preparation. The results showed that the internship programs contributed to improving document organization, facilitating access to informtion, and enhancing the effectiveness of administrative management. Therefore, internship programs can serve as a learning medium while also supporting the strengthening of administrative governance within the company